Elementary school students and their perceptions of Brazilian natives - Souza, Victor Gustavo de [UNESP] (Univ Brasilia, 2020)
This article presents the results obtained from a block of history classes, taught to students in the 5th year of elementary school, whose main theme was the discussion on the perceptions that students have about Brazilian indigenous communities and the promotion of breaking stereotypes through historical awareness. Jean Baptist-Debret paintings, dating from the 19th century, and 21st century photographs, which show the native in contact with contemporary technologies, were adopted as sources. The classes demonstrated that the popular mentality still sees indigenous peoples through colonial eyes and it is difficult to understand their place in contemporary society.
Keywords: History teaching; Brazilian natives; Elementary school